Analisis Pemilihan Supplier dengan Metode AHP dan Model QCDFR di PT. Novalindo Sukses Mandiri - Oktavian, Aditya; Pradipto, Masri; Borman, Mohammad Riski; Hartini, Sri; Sari, Tri Novita; Farhana, Adinda; Rosalina, Uki Aulia (Universitas Kadiri, 2025)
The selection of raw material suppliers affects production efficiency. PT. Novalindo only considers price, neglecting quality, delivery, flexibility, and responsiveness. This study uses AHP based on QCDFR for a systematic solution. The study begins with assessing stainless steel and iron plate suppliers based on QCDFR criteria, followed by the application of AHP to determine the best supplier, calculate criterion weights, and perform consistency testing. The study shows that PT. Yunsung is the best supplier for both iron and stainless steel plates with a weight of 0.504. PT. Bansoek and CV. Mulya rank second and third with weights of 0.290 and 0.170, respectively. PT. Yunsung excels in the quality, cost, and flexibility criteria, while CV. Mulya excels in delivery, and PT. Bansoek excels in responsiveness. The consistency of criterion weightings for both types of plates shows acceptable consistency values of 0.015 and 0.013. This study provides a systematic, data-driven solution for selecting the best supplier for manufacturing companies in the iron and stainless steel plate sector, offering a strategy for evaluating and selecting suppliers across multiple dimensions, including quality, cost, delivery, flexibility, and responsiveness. The study has been able to improve operational efficiency and reduce the risk of supply chain disruptions.